The Impact of Timber Exports on Economic Growth in Cameroon: An Econometric Investigation - Forgha, Njimanted Godfrey; Aquilas, Nkwetta Ajong (Asian Journal of Economic Modelling, 2015)
Cameroon, one of the most likely natural resources-based economies in Africa rely on its natural resource exports for growth. With the fall in international oil prices in Cameroon in the late 1980’s, timber resources emerged as one of the major sources of foreign earnings.Since then, statistics reveal that timber exports have grown in volume,constitutinglargely of unprocessed and semi-processed wood products, with little value-added. This study, therefore examines the impact of timber export on economic growth in Cameroon over 34 years (1980 to 2014 inclusive) using time series data from the Food and Agricultural Organization and World Development Indicators. Using the Johansen Cointegration and Error Correction Modelling, the results show that timber export have an insignificant effect on the economic growth of Cameroon in the short run and in the long run it has a significant positive effect. We therefore recommend the increased consumption of locally-manufactured wood products, limitation of imported manufactured wood products, as well as encouraging the establishment of locally-based wood processing industries.